2000
DOI: 10.1007/pl00013435
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable response to cyclophosphamide in steroid-dependent nephrotic syndrome

Abstract: Development of steroid dependency represents a significant therapeutic challenge in steroid-sensitive nephrotic syndrome. Previous studies have shown conflicting results concerning the benefit of a 12-week treatment with cyclophosphamide (CPO), with 24%-67% of patients achieving long-term remission. We therefore analyzed the clinical response of 20 consecutive children with steroid-dependent nephrotic syndrome (SDNS) (12 male, median age at start of treatment 5.9 years, range 3.2-14.7 years) treated at our ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 0 publications
1
27
2
Order By: Relevance
“…In the Prasad et al study [19], renal biopsy was only performed for 54% of patients; 36% of them had focal segmental glomerulosclerosis, while all our patients had biopsy-proven MCNS. Additionally, racial and genetic factors may alter the pattern of response to therapy so that the widely variable response rate to oral cyclophosphamide therapy seen in these patients reported in the literature (19%-75% at 1-3 years [19,20,21,22,23,24,25,26,27]) may be extrapolated to intravenous form. Furthermore, the conclusion of the previous two studies [4,19], that the I.V.…”
Section: Discussionmentioning
confidence: 92%
“…In the Prasad et al study [19], renal biopsy was only performed for 54% of patients; 36% of them had focal segmental glomerulosclerosis, while all our patients had biopsy-proven MCNS. Additionally, racial and genetic factors may alter the pattern of response to therapy so that the widely variable response rate to oral cyclophosphamide therapy seen in these patients reported in the literature (19%-75% at 1-3 years [19,20,21,22,23,24,25,26,27]) may be extrapolated to intravenous form. Furthermore, the conclusion of the previous two studies [4,19], that the I.V.…”
Section: Discussionmentioning
confidence: 92%
“…However, the risk of developing malignancy and gonadal toxicity in adolescent children and the poor responsiveness in patients with steroid dependent NS or steroid resistant NS to these agents have limited their use. [12][13][14][15] In an attempt to improve the management of these patients, CsA was first used in 1985 in children with NS. Since then, numerous reports have shown that CsA is effective in children with steroid dependent NS and steroid resistant NS to relieve steroid toxicity and to achieve remission, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For these patients various therapeutic strategies have been suggested, including other immunosuppressive agents such as tacrolimus [3] or mycophenolate mofetil [4,5], or the immunostimulatory drug levamisole [6]. However, these strategies often fail to maintain complete remission of nephrotic syndrome [7].…”
Section: Introductionmentioning
confidence: 99%